A Fingerprint Representation Technique based on Minutiae Quadrilateral Structure - Menaria, L; Jain, K (International Journal of Computer Sciences and Engineering, 2025)
Fingerprint is a popular biometric trait which is used extensively in several applications for person authentication, providing high uniqueness and acceptable performance. The goal of any fingerprint representation is to capture as much of the unique information available in a fingerprint while discarding the variations between multiple impressions of the same finger. In this paper, we propose a new alignment-free fingerprint representation using the quadrilateral structure. We construct the feature set from the quadrilateral structure. The constructed feature set is quantised and mapped to a pre-defined 3D array. By sequentially visiting the cells of the 3D array, a fixed length 1D bit string is generated. This bit string is applied with DFT to generate a complex vector and the complex vector is multiplied with a random matrix generated by user’s key, to generate a final cancellable template. The proposed method FS_QUAD is tested on FVC 2002 databases and results show satisfactory performance.